Spin-coated high mobility MoO3 thin film for designing highly efficient lead-free perovskite solar cells - Islam M.A.; Siddiquee I.A.; Wahab Y.A.; Hatta S.F.W.; Imam J.M.; Low F.W.; Ahamed A.; Alam M.N.-E. (Elsevier Ltd, 2025)
Among the thin film-photovoltaics, perovskite solar cells (PSCs) are one of the most developing topics of research in recent times. Research records reveal that around 26 % efficiency in PSCs has already been achieved so far. However, the commercialization of those PSCs is hindered due to the toxicity of lead (Pb), and the instability of organic cations as well as structural volatility. Several inorganic materials including inorganic hole transport layer (HTL) have recently been proposed and developed to reduce the organic part in the device structure. We fabricate MoO3 thin film materials and conduct a detailed study to realize the potential of MoO3 as a unique HTL for application in PSCs. The synthesis of MoO3 thin film includes several characterization techniques e.g. XRD, FESEM, EDX, UV?Vis, and Hall Effect measurement. We design a MoO3 thin film-based, lead-free PSC structure of FTO/MoO3/PTAA/(FA)2BiCuI6/ZnO/Ag and perform numerical analysis using the SCAPS-1D simulation tool. In the device simulation process, we use the experimentally obtained optoelectrical properties of the MoO3 film and achieve a maximum efficiency of around 22.28 % in a contained lead-free PSC. ? 2024 The Author(s)